2000
DOI: 10.1097/00003072-200006000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Indium-111–Labeled Hepatocytes to Determine the Biodistribution of Transplanted Hepatocytes Through Portal Vein Infusion

Abstract: These results indicate that In-111 labeling of hepatocytes is useful for the short-term noninvasive analysis of the biodistribution of transplanted hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…28,29 Previous studies have shown that rodent and human hepatocytes effectively incorporate 111 In and 99m Tc labels. 31,33,36 Similarly, leukocytes and other cells incorporate 111 In and 99m Tc labels, and bone marrow-derived mesenchymal stem cells incorporate 99m Tc-exametazime. [37][38][39] In contrast, mouse and rat LSEC incorporated 111 In-oxine but not 99m Tc.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Previous studies have shown that rodent and human hepatocytes effectively incorporate 111 In and 99m Tc labels. 31,33,36 Similarly, leukocytes and other cells incorporate 111 In and 99m Tc labels, and bone marrow-derived mesenchymal stem cells incorporate 99m Tc-exametazime. [37][38][39] In contrast, mouse and rat LSEC incorporated 111 In-oxine but not 99m Tc.…”
Section: Discussionmentioning
confidence: 99%
“…After re-establishing intercellular contacts with neighboring hepatocytes and connecting to the biliary and vascular systems, transplanted cells are functionally and histologically indistinguishable from endogenous hepatocytes [59]. Excellent evidence that the cells delivered via the portal vein do not readily pass through the liver to extrahepatic sites was provided when human hepatocytes, labeled with indium-111 oxyquinoline, were infused in a 5-year- old child with urea cycle defect [62]. …”
Section: Cell Dose and Route Of Administrationmentioning
confidence: 99%
“…Novel noninvasive methods to label and monitor cell survival and engraftment after transplantation are also currently under investigation [107]. As mentioned, radioisotopes have been successfully used in clinical settings to demonstrate hepatocyte distribution after transplantation [62]. In addition, MRIs of donor cells previously loaded with iron oxide particles [108,109] will likely be investigated in clinical transplants.…”
Section: Evaluation Of Sustained Engraftmentmentioning
confidence: 99%
“…[ 111 In]indium oxine ( 111 In-oxine) has been widely accepted for safe radiolabeling of leukocytes to localize areas of inflammation. 6 -8 Moreover, 111 In-oxine has been used to determine the biodistribution of transplanted hepatocytes 9 or dendritic cells. 10,11 Therefore, we investigated whether radioactive labeling with 111 In-oxine might provide a clinically applicable tool to monitor the fate of transplanted EPCs in living rats after myocardial infarction.…”
mentioning
confidence: 99%